Supplementary Material: Radiometric Calibration from Faces in Images - Li, Chen; Lin, Steve; Zhou, Kun; Ikeuchi, Katsushi (2008)
key step to our approach is identifying the single pigment density change map C and we describe it in Sec. 5.1 in the main paper. We use the pseudo-albedo ˆA by applying intrinsic image decomposition on the uncalibrated image I instead of the skin albedo A. We show that the an accurate identification of C can be obtained only using ˆA.